KAJIAN PRAKTIK PEMBELAJARAN DI SD NEGERI 010 SEPAKU: ANALISIS PERMASALAHAN PEMBELAJARAN SEBAGAI DASAR IMPLEMENTASI MODEL PEMBELAJARAN 4SI - Nafiah; Adi Winanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the Independent Curriculum emphasizes on student-centered learning. However, there are still a number of issues with elementary school education, including inadequate use of media, context-deficient learning modules, and assessments that serve merely as a means of assigning marks. This study aims to analyze learning practices at SDN 010 Sepaku and identify the various problems faced by teachers in learning process and formulate a 4SI (Clue identification, cultural exploration, visual creation and presentation) as a learning innovation developed based on real needs in elementary schools. This study uses a qualitative descriptive approach with a case study method. The data were collected through observation, interviews, documentation studies, and questionnaires, then analyzed descriptively. The findings of this study indicate that although the school has sufficient facilities and a favorable learning environment, student-centered learning methods still require improvement. The implementation of 4SI model can improve the involvement, curiosity, creativity, collaboration, and self-confidence of students, thus potentially supporting the implementation of the Independent Curriculum in elementary schools.